Shifting Trend on Management Event during the Pandemic - Nining Yuniati; Kadek Ratih Dwi Oktarini; Raden Ayu Trisnayoni (International Journal of Applied Sciences in Tourism and Events, 2022)
The shift in trends in organizing MICE events which are conventionally known as mass gathering activities and as a result of the pandemic there have been changes. This already happened in all countries in the world which then responded with various policies to maintain business sustainability despite being pessimistic. Stakeholders are hesitant in changing the paradigm of MICE activities from conventional models to virtual or hybrid models. This doubt is caused by the advantages and disadvantages of each type of event which will most likely reduce business profits. A simple literature review known as feature selection is used to find answers to this problem. Based on the analysis it was found that event activities are now popular in virtual and hybrid ways. Both virtual and hybrid events have changed the conventional perspective of understanding events. Although the implementation is simpler, the two events have a smaller economic impact compared to regular events that were popular in the pre-pandemic era. This paper also tries to find case studies in several countries that have successfully organized MICE events during the pandemic. In the end, a new taxonomy of event management emerged, namely original (regular) events, virtual events, and hybrid events. This change in the landscape of organizing MICE events will be an important consideration for MICE business people who may experience stagnation in recent times due to the Covid-19 pandemic.